(untitled) (Journal of Human Sciences, 2019)
(The study aimed to identify the reality of strategic planning Social Security Fund in Sebha The researcher used the analytical descriptive approach. Further, questionnaire was used as the main instrument for data collection. Study population consisted of (400) individuals and a stratified random sample was chosen. The number of analyzed questionnaires was (33) questionnaires. The SPSS was used to enter and process data and test hypotheses. The study found that Social Security Fund in Sebha practice strategic planning at different levels. In addition, the Fund have a strategic direction and philosophy and pay much attention to the actual practices of strategic planning. There is a significant difference between the exercise of strategic planning in the Social Security Fund due to variable (age), and there is no significant difference to the rest of the other variables (gender, experience - educational level).